2004
DOI: 10.1063/1.1667281
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling spectroscopy under pulsed spin injection

Abstract: An experimental technique combining cryogenic scanning tunneling spectroscopy ͑STS͒ and pulsed quasiparticle spin injection has been developed. The spin injection is intended to perturb a superconducting thin film from spin equilibrium, while the STS monitors its steady-state quasiparticle spectrum. A pulsed injection circuit was designed to minimize Joule heating while being both synchronized with and decoupled from the STS circuitry. A detailed description of the technique is presented, along with its applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Spin injection depletes the superconducting condensate and can result in switching to a normal state of much higher resistance (Dong et al, 1997;Vas'ko et al, 1997;Takahashi et al, 1999;Wei et al, 1999;Yeh et al, 1999). A critical review of possible spurious effects in reported experiments (Gim et al, 2001) has also stimulated the development of a novel detection technique which uses scanning tunneling spectroscopy combined with pulsed quasiparticle spin injection to minimize Joule heating (Ngai et al, 2004;see Sec. IV.A.1).…”
Section: F/n Junctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spin injection depletes the superconducting condensate and can result in switching to a normal state of much higher resistance (Dong et al, 1997;Vas'ko et al, 1997;Takahashi et al, 1999;Wei et al, 1999;Yeh et al, 1999). A critical review of possible spurious effects in reported experiments (Gim et al, 2001) has also stimulated the development of a novel detection technique which uses scanning tunneling spectroscopy combined with pulsed quasiparticle spin injection to minimize Joule heating (Ngai et al, 2004;see Sec. IV.A.1).…”
Section: F/n Junctionmentioning
confidence: 99%
“…IV.A.3), which, in addition to the usual quasiparticle tunneling, contributes to the I-V characteristics of a F/I/S junction (Hu and Yan, 1999;Kashiwaya et al, 1999;Zhu et al, 1999;Valls, 1999, 2000; a simpler N/I/S case is reviewed by Hu, 1998 andTanaka, 2000). The suppression of a zero-bias conductance peak, measured by a scanning tunneling microscope, was recently used to detect spin injection into a high-temperature superconductor (Ngai et al, 2004).…”
Section: F/i/s Tunnelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest to study spin accumulation, one of the key elements in spintronic applications [1], is not limited to novel spin-based devices. Spin injection can also be used as a sensitive spectroscopic tool to study fundamental properties such as the pairing symmetry of unconventional superconductors [2,3], Skyrmion excitations in the quantum Hall regime [4,5], and spincharge separation in non-Fermi liquids [6,7]. While spin accumulation in metals was first demonstrated by Johnson and Silsbee [8], the basis for understanding spin injection and, more generally, spin-polarized transport, dates back to Mott [9].…”
mentioning
confidence: 99%
“…7 was done on YBa 2 Cu 3 O 7−␦ under a spin-injected current. 9 It would be interesting to see a similar experiment performed on an HTS sample carrying a supercurrent in the near future. As a natural extension of our previous work, 7 here we examine the LDOS induced by a strong defect which replaces a Cu 2+ ion in the top CuO layer of a current carrying HTS.…”
mentioning
confidence: 99%